Cholesterol Prognostic Value in Severe Postoperative Patient´s Morbidity and Mortality - Daymara del Río Bazán; Maricela Morera Pérez; Georgia Díaz-Perera Fernández (Revista Finlay)
Background: metabolic disorders occur in severe postoperative patients, one of them is related to the lipid profile. Hypercholesterolemia in these patients is associated with a worse prognosis. Objective: to describe the prognostic value of cholesterol levels in the morbidity and mortality of patients treated in intensive care at the Minimal Access Surgery National Center in Havana. Method: a descriptive, retrospective research was carried out at the Minimal Access Surgery National Center between 2020 and 2021. The study included severely postoperative adults. Demographic, clinical and laboratory variables were analyzed. The information was entered into a relational database, created according to the IBM SPSS 21 program, and statistical analysis was carried out. Results: the percentage of complications, sepsis, the APACHE scale and the length of stay were greater in patients with the presence of hypercholesterolemia. The deceased patients exhibited the lowest cholesterol levels compared to the patients who were discharged alive. Conclusions: in severe postoperative patients, hypercholesterolemia implies a worse prognosis, it should be considered in the evolution of these patients. Incorporating it into the periodic follow-up would allow the early diagnosis of complications and reduce mortality.